2022
DOI: 10.3389/fpsyg.2022.921285
|View full text |Cite
|
Sign up to set email alerts
|

Linking Exercise Intention to Exercise Action: The Moderating Role of Self-Efficacy

Abstract: As physical exercise benefits both physical and psychological health of college students, it is important to promote the habit of physical exercise among them. This study adopted the Health Action Process Approach (HAPA) model to understand the exercise intention–action link and determine the moderating role of self-efficacy. We recruited 242 students from a university in China and asked them to complete a six-wave survey. The survey results indicated that exercise intention was positively related to both copi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 47 publications
0
6
0
Order By: Relevance
“…However, the ESES used in the studies, differed in items or measurement scale. Also other studies (Gong & Sheng, 2022;Hou, Li, Zheng, Qi, & Zhou, 2022;Lawrence et al, 2022;Lee, Bae, & Jang, 2022;Lee & Young, 2018;Marcus & Forsyth, 2018;Parsons, et al, 2019;Wang et al, 2019;Xue-Liu & Mu, 2021) considered selfefficacy measurement tools with items of questions about physical activity specifically (n = 6), including separate questions about physical activity selfefficacy as part of the questionnaire or survey used in the study (n = 4). One study (Tang, Chen, Wang, Lu, & Yan, 2022) focused on emotional self-efficacy measures.…”
Section: Research Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the ESES used in the studies, differed in items or measurement scale. Also other studies (Gong & Sheng, 2022;Hou, Li, Zheng, Qi, & Zhou, 2022;Lawrence et al, 2022;Lee, Bae, & Jang, 2022;Lee & Young, 2018;Marcus & Forsyth, 2018;Parsons, et al, 2019;Wang et al, 2019;Xue-Liu & Mu, 2021) considered selfefficacy measurement tools with items of questions about physical activity specifically (n = 6), including separate questions about physical activity selfefficacy as part of the questionnaire or survey used in the study (n = 4). One study (Tang, Chen, Wang, Lu, & Yan, 2022) focused on emotional self-efficacy measures.…”
Section: Research Resultsmentioning
confidence: 99%
“…Self-efficacy is the most frequently identified psychosocial determinant of physical activity. Researches (Gong & Sheng, 2022;Hou, Li, Zheng, Qi & Zhou, 2022;Wang et al, 2022a;Xue-Liu & Mu, 2021) show that self-efficacy frequently influences or mediates physical activity behavior.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, exercise intention can predict the generation of exercise behavior, and a large number of studies have confirmed that exercise intention is an effective predictor of exercise behavior (Chen et al, 2022;Teixeira et al, 2022;Zhang et al, 2022). Hou et al (2022) confirmed in a study of 242 college students in China that exercise intention can effectively predict exercise behavior. Gu et al (2022) found that exercise attitude was a significant predictor of exercise behavior based on TPA during COVID-19.…”
Section: Exercise Intention and Exercise Behaviormentioning
confidence: 87%
“…Previous studies have shown that self-e cacy plays a regulatory role between exercise intention and exercise behavior. Students with high-level self-e cacy show a stronger relationship between planning and action (Hou et al, 2022). Then, can action selfe cacy regulate the relationship between exercise social support and exercise behavior?…”
Section: Moderating Effect Of Action Self-e Cacymentioning
confidence: 99%